The territorial attractiveness of foreign direct investment in Morocco: incentive policies and obstacles. - (:unkn) unknown (My University, 2024)
The highly competitive environment that characterises today's world has made the attractiveness of territories a major objective of countries' territorial policies. Following the example of several developing nations, the desire to build attractive regions for economic activities and mobile production factors (companies, entrepreneurs, capital, etc.) has led the Kingdom of Morocco to place this notion at the centre of its concerns. The Moroccan territory, being one of the strategic economic bridges between Africa and Europe, will be the subject of our present article. For the benefit of local and regional decision-makers, investors and researchers, we propose a complement to the current state of the art of the territorial attractiveness of foreign direct investment by offering both a state of the art on the concept of territorial attractiveness, and a documentary and exploratory study of incentive policies and obstacles to investment in Morocco. The methodological approach on which we based ourselves is the exploratory approach through individual interviews with territorial actors in charge of promoting the Moroccan territory. We have also supplemented our study with research documents available on the Internet from national and international institutions, more specifically the Directorate of Foreign Investment and the Regional Investment Centres in Morocco. The first part of this work is mainly based on a literature review analysing the concept of territorial attractiveness. Then, a real case study will be proposed, based on an exploratory study (qualitative interviews) on the Moroccan territory, while analysing its attractiveness and its investment climate. The aim is to highlight the key success factors to be promoted and the development avenues to be put in place. As the royal gateway to Africa, the country boasts one of the most attractive territorials offers and is positioned as a booming economic hub between Europe and Africa. This is thanks to
Keywords: African Research